Proceedings of the 5th International Conference on Education and Technology (ICET 2019) 2019
DOI: 10.2991/icet-19.2019.136
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Pro-social Behavior and The Implication of Guidance and Counseling

Abstract: The aim of this study is to describe the pro-social behavior of high grade elementary school students and the implications of guidance and counseling services. The study uses a quantitative approach with descriptive methods. The research subjects totaled 65 students as sample saturated. The research instrument used the scale of students' pro-social behavior. Data analysis was performed by calculating the average and standard deviation, so that the categorization was obtained. The results showed that pro-social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Regarding the role of teacher-student relationship, previous studies (Jadoon et al, 2022;Konow, 2019;Longobardi et al, 2021) have confirmed that there is a significant positive correlation between teacher-student relationship and prosocial behavior, namely, harmonious teacher-student relationship is an important predictor of prosocial behavior. In addition, many studies have found that teaching behavior (Hudzaifah, 2021;Mujahidin et al, 2021;Yustiana et al, 2019;Zhang & Zhang, 2021) and classroom evaluation method (Cheon et al, 2018) affect the prosocial behavior of college students. Therefore, this study reports that the moral teaching behavior of teachers and the prosocial behavior of college students are important and proposes the following research hypothesis.…”
Section: Teacher Moral Teaching Behavior and College Students Prosoci...mentioning
confidence: 99%
“…Regarding the role of teacher-student relationship, previous studies (Jadoon et al, 2022;Konow, 2019;Longobardi et al, 2021) have confirmed that there is a significant positive correlation between teacher-student relationship and prosocial behavior, namely, harmonious teacher-student relationship is an important predictor of prosocial behavior. In addition, many studies have found that teaching behavior (Hudzaifah, 2021;Mujahidin et al, 2021;Yustiana et al, 2019;Zhang & Zhang, 2021) and classroom evaluation method (Cheon et al, 2018) affect the prosocial behavior of college students. Therefore, this study reports that the moral teaching behavior of teachers and the prosocial behavior of college students are important and proposes the following research hypothesis.…”
Section: Teacher Moral Teaching Behavior and College Students Prosoci...mentioning
confidence: 99%